Comparative study on outcomes between open reduction and internal fixation with plating and K-wires plus casting for distal end radius fractures - Sudheer Kumar,; Vijaya Kumar Gannu,; Raju Rayapuram,; Muralidhar Bandi, (Asian Journal of Medical Sciences, 2024)
Background: Distal end radius fractures are common injuries treated in orthopedic practice, with varying treatment modalities influencing outcomes. Aims and Objectives: The study was designed to compare the outcomes between open reduction and internal fixation (ORIF) with plating and K-wires plus casting in patients treated for distal end radius fractures. Materials and Methods: One hundred patients with distal end radius fractures were included and divided into two groups: Group A (ORIF with plating) and Group B (K-wires plus casting), with 50 patients in each group. Parameters included were healing time, complication rates, functional recovery, patient satisfaction scores, pain levels during recovery, and the time to return to daily activities. Results: Group A demonstrated a shorter average healing time (8 weeks) compared to Group B (9 weeks). Complication rates showed 5% malunion and 4% delayed union in Group A, against 12% and 6%, respectively, in Group B. Functional recovery was higher in Group A, with 93% grip strength and 88% range of motion recovery. Patient satisfaction was also higher in Group A (8.5 out of 10) compared to Group B (7.5 out of 10). Pain levels during recovery were lower in Group A, and the time to return to daily activities was shorter (8 weeks for Group A versus 10 weeks for Group B). Conclusion: The study suggests that ORIF with plating offers better outcomes in terms of healing time, complication rates, functional recovery, patient satisfaction, pain management, and quicker return to daily activities than K-wires plus casting for distal end radius fractures.